Effect of PH and temperature on anaerobic digestion of solid waste containing cellulose and proteins - Chung, Tran Duc (2007)
One of the main approaches to solid waste management in growing cities in the Philippines, Vietnam and other Southeast Asian countries is to develop compact solid waste treatment systems. Such systems must operate at high treatment rate so that their space requirement is small. To achieve high rate of degradation and stabilization of organic solid wastes, the bioreactor system must operate at optimum pH and temperature conditions. Hence, this study investigated the effects of pH and temperature on the degradation of cellulose and nitrogen-rich solids.Three sets of duplicated batch reactors were set up at varying temperature (30,32 and 37̊C) and pH (6.5, 7.0 and 7.5 ). The batch reactors contained cellulose particles and ground lean pork meat to simulate the degradation of solid waste containing cellulose and proteins as in the co-digestion of organic fraction of municipal solid waste (OFMSW) and slaughterhouse or meat-processing waste. The rate of methane production and the hydrolysis kinetic equation constants were determined at the different pH and temperature levels. The results showed that methane production was best at initial pH 7.0 (7.3±0.2 during 8 days run) and initial pH 7.5 (7.8±0.2 during 8 days run) for 37̊C. At the same time pH level, the rate of hydrolysis was higher at 32̊C than 30̊C and 37̊C. At 32 and 37̊C, hydrolysis rate was lowest at pH 6.5 than 7.0 and 7.5. The results further showed that the first-order hydrolysis rate equation, which is the generally accepted model for hydrolysis, fits only a certain period of the hydrolysis curve indicating that the first-order hydrolysis constant changes as the nature of the remaining solid also changes
Thesis (M.S. Environmental Engineering)--University of the Philippines Diliman.
Keywords: Sewage -- Purification -- Anaerobic treatment; Organic wastes -- Purification